Evolving engineering education: online vs. in-person capstone projects compared (EEE-OIPC) - Znidi, Faycal; Uddin, Md. Nizam; Morsy, Mohamed (Frontiers in Education, 2024)
This study examines the effectiveness of online and face-to-face (F2F) instructional methods in Capstone Senior Design (CSD) projects within Electrical Engineering (EE) and Mechanical Engineering (ME). It explores how each mode influences student success and learning outcomes, addressing the need for adaptable teaching strategies in science, technology, engineering, and mathematics (STEM) education. A comprehensive assessment was conducted, which included project evaluations, advisor feedback, and self-peer reviews. This multifaceted approach aimed to gauge the relative efficacy of online versus F2F modalities in supporting educational outcomes. The findings indicated that both online and F2F modalities achieved parity on several metrics. However, F2F settings significantly enhanced teamwork and collaboration among students. In contrast, online environments excelled in advisor evaluations, suggesting effective mentorship despite less consistent teamwork and project execution. The results emphasize the potential benefits of integrating online and traditional pedagogies to improve educational strategies and student learning experiences. The study highlights the importance of developing online instructional strategies that better mimic the collaborative advantages of F2F instruction. It also underscores the need for a holistic approach to curriculum development to prepare STEM students effectively for future challenges.